Upaya Peningkatan Kualitas Sumber Daya Manusia Pada Taman Pendidikan Al-Quran - Rudiatno; Aldea Mita Cheryta (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The application of human resource management at the educational level is an activity that has the scope of employees, managers, laborers, and workers as an effort to maintain the stability of organizational activities and relations between institutions. The urgency of this research is a discussion about increasing the increase in human resources in TPQ. This increase in human resources correlates with the skills of students who carry out learning, besides that students are expected to be more responsive and get good knowledge. The formulation of the problem studied in the study includes: 1) 1) How is the sustainability of human resources for the management of TPQ Bahrul Ulum, Gresik Regency? 2) What is the strategy to improve the management of TPQ Bahrul Ulum, Gresik Regency? The research method uses qualitative with a focus on the use of in-depth interviews, documentation and observation. This research approach method uses continuous improvement of literacy, this is possible because the focus of research refers to increasing human resources in TPQ management. Data analysis techniques that include: 1) Data Collection; 2) Data Reduction; 3) Display Data; 4) Drawing Conclusions. The result is that the need for the preparation and development of curricula that are relevant to the needs of students, as well as the application of creative and effective teaching methods, can increase the interest and participation of students in Islamic religious learning. The role of parents and the community is important to contribute to creating a positive and supportive learning environment for improving the quality of human resources at TPQ Bahrul Ulum.